2015
DOI: 10.1111/risa.12346
|View full text |Cite
|
Sign up to set email alerts
|

The Inverse Relation Between Risks and Benefits: The Role of Affect and Expertise

Abstract: Although risk and benefits of risky activities are positively correlated in the real world, empirical results indicate that people perceive them as negatively correlated. The common explanation is that confounding benefits and losses stems from affect. In this article, we address the issue that has not been clearly established in studies on the affect heuristic: to what extent boundary conditions, such as judgments' generality and expertise, influence the presence of the inverse relation in judgments of hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…While participants were not put in a negative mood, negative affect around driving may have still led to a more careful analysis of risks and benefits of self‐driving cars. And, when participants make judgments on a more concrete level, previous research has found that the inverse relationship of risk and benefit perceptions is reduced or eliminated (Sokolowska & Sleboda, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While participants were not put in a negative mood, negative affect around driving may have still led to a more careful analysis of risks and benefits of self‐driving cars. And, when participants make judgments on a more concrete level, previous research has found that the inverse relationship of risk and benefit perceptions is reduced or eliminated (Sokolowska & Sleboda, ).…”
Section: Discussionmentioning
confidence: 99%
“…If people's emotional responses are more positive, they tend to judge risks to be lower and benefits to be higher; the more negative people's affective reactions are, the more likely they are to judge risks to be higher and benefits to be lower (Alhakami & Slovic, ; Slovic et al., ). People may be particularly more likely to rely on their affective reactions as a common source to generate both their risk and benefit evaluations when they lack expertise within a given domain (Finucane, Alhakami, Slovic, & Johnson, ; Sokolowska & Sleboda, ).…”
Section: Introductionmentioning
confidence: 99%
“…The term “inverse relation” describes the tendency to judge some risky activities as very high in danger and very low in benefits, and some other activities as low in danger and high in benefits. In the last 4 decades, the inverse relation has been observed in many studies related, for example, to the financial domain (e.g., Bowman, 1980; Kempf et al, 2014; Shefrin, 2001), environmental hazards (e.g., Alhakami & Slovic, 1994; Fischhoff et al, 1978; Slovic et al, 1991), and new technologies (e.g., Savadori et al, 2004; Sokolowska & Sleboda, 2015). The inverse relation is usually interpreted in terms of the affect heuristic (Alhakami & Slovic, 1994; Finucane et al, 2000; Slovic et al, 2002) according to which the perception of risk and benefits is linked to a person’s overall affective evaluation of an activity.…”
Section: The R–v Relation and Preferencesmentioning
confidence: 98%
“…Studies have typically documented an inverse relationship between risks and benefits, in which hazards are either judged as high in danger and low in benefits, or low in danger and high in benefits [ 1 6 ]. This inverse risk-benefit relation has been examined in relation to numerous hazards, including environmental hazards [ 1 , 7 ] and new technologies [ 8 ], as well as in judgements in the area of finance [ 9 – 11 ]. For example, Fischhoff and collaborators [ 1 ] found that motorcycles and nuclear power are judged as very low in benefits and very high in risks, while antibiotics and vaccinations are perceived as high in benefits and low in risks.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, researchers have expected that experts, when judging risks and benefits of technologies, will be more likely to relay on their knowledge and experience and therefore make less biased but more rational judgements. Some studies have reported experts and laypeople to differ in their risk perception, for example when judging chemical products, nuclear power, police work, surgery, electric power, X-rays and swimming [ 22 , 23 ], mountain climbing [ 23 ], hunting, bicycles, and spray cans [ 22 ], as well as in the inefficacy of health services and the storage of medical equipment [ 24 ], other researchers documented no differences between experts and the public in risk perception [ 7 , 8 , 25 ]. Thus, evidence of the impact of expertise on risk-benefit judgements is inconclusive [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%